The quality of human capital and economic growth in Mexico - Ocegueda Hernández, Juan Manuel; Ocegueda Hernández, Marco Tulio (Estudios Económicos de El Colegio de México, 2024)
The relationship between human capital and economic growth in Mexico is analyzed using panel data by states. The effects of schooling are measured by educational level and controlled for differences in the quality of human capital with two alternative variables: the PISA exam score in mathematics and the added value attributable to human capital within total salaries. It is concluded that the discrepancies in the quality of human capital and the differentiated advances in higher education enrolment rate, determined that the educational effort of the last two decades had disparate regional effects on economic growth.